Glucose reactivity with filling materials as a limitation for using the glucose leakage model - Shemesh, H.; Souza, E. M. [UNESP]; Wu, M. -K.; Wesselink, P. R. (Wiley-Blackwell, 2008)
Aim To evaluate the reactivity of different endodontic materials and sealers with glucose and to asses the reliability of the glucose leakage model in measuring penetration of glucose through these materials.Methodology Ten uniform discs (radius 5 mm, thickness 2 mm) were made of each of the following materials: Portland cement, MTA (grey and white), sealer 26, calcium sulphate, calcium hydroxide [Ca(OH)(2)], AH26,Epiphany, Resilon, gutta-percha and dentine. After storing the discs for 1 week at 37 degrees C and humid conditions, they were immersed in 0.2 mg mL(-1) glucose solution in a test tube. The concentration of glucose was evaluated using an enzymatic reaction after 1 week. Statistical analysis was performed with the ANOVA and Dunnett tests at a significant level of P < 0.05.Results Portland cement, MTA, Ca(OH)(2) and sealer 26 reduced the concentration in the test tube of glucose significantly after 1 week (P < 0.05). Calcium sulphate reduced the concentration of glucose, but the difference in concentrations was not significant (P = 0.054).Conclusions Portland cement, MTA, Ca(OH)(2) and sealer 26 react with a 0.2 mg mL(-1) glucose solution. Therefore, these materials should not be evaluated for sealing ability with the glucose leakage model.
Keywords: glucose; leakage model; optical density; reactivity